2018
DOI: 10.1016/j.bbamcr.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of arsenic with gap junction protein connexin 43 alters gap junctional intercellular communication

Abstract: Chronic exposure to Arsenic pollution in ground water is one of the largest environmental health disasters in the world. The toxicity of trivalent Arsenicals primarily happens due to its interaction with sulfhydryl groups in proteins. Arsenic binding to the protein can change the conformation of the protein and alter its interactions with other proteins leading to tissue damage. Therefore, much importance has been given to the studies of Arsenic bound proteins, for the purpose of understanding the origins of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…To this regard, significant enhancement of the expression profiles of Cx40 , Cx43 and Cx45 connexin genes and of Cx43 protein, paralleled by large Cx43 immunofluorescence signals, might contribute to the remodeling of gap junctions leading to abnormal cardiomyocyte conduction properties. In support of our hypothesis, structural model studies showed that arsenic can directly bind to Cx43 channels potentially causing conformational changes in their structure 34 . However, on the basis of our results, we cannot determine whether enhancement of connexins expression is a result or a cause of changed contraction, or even an unrelated effect.…”
Section: Discussionsupporting
confidence: 74%
“…To this regard, significant enhancement of the expression profiles of Cx40 , Cx43 and Cx45 connexin genes and of Cx43 protein, paralleled by large Cx43 immunofluorescence signals, might contribute to the remodeling of gap junctions leading to abnormal cardiomyocyte conduction properties. In support of our hypothesis, structural model studies showed that arsenic can directly bind to Cx43 channels potentially causing conformational changes in their structure 34 . However, on the basis of our results, we cannot determine whether enhancement of connexins expression is a result or a cause of changed contraction, or even an unrelated effect.…”
Section: Discussionsupporting
confidence: 74%
“…The media was discarded, cells were washed with 1 × PBS and 200 µl of fresh media containing (5 mg/ml) of MTT (Thiazolyl Blue Tetrazolium Bromide) was added to each well and incubated at 37 • C with 5% CO 2 for 5 h. The entire solution was discarded carefully without disturbing the purple-colored formazan crystals formed on the surface of the well. Hundred micro-liter of DMSO was added to each well, and absorbance was measured at 570 nm using an Absorbance Plate Reader (Hussain et al, 2018). Net survival values were calculated and plotted using GraphPad Prism 6.0., Maximum non-cytotoxic concentration (MNCC) dose and effective concentration (EC 50 ) of NBE were determined in Neuro-2A cells.…”
Section: In Vitro Cell Viability Assaymentioning
confidence: 99%
“…After Cx43 translation and post-translational modification in the endoplasmic reticulum (ER), Cx43 oligomerizes into hexamers as gap junction hemichannels in the Trans-Golgi Network (TGN) ( Musil and Goodenough, 1993 ; Hussain et al, 2018 ). The hemichannels are then trafficked to cell membrane at cell-cell borders along microtubule “highways” ( Shaw et al, 2007 ; Basheer and Shaw, 2016 ).…”
Section: Full-length Cx43 Traffickingmentioning
confidence: 99%